Recurrent Miscarriage: Diagnostic and Therapeutic Procedures. Guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry Number 015/050) - Toth, Bettina; Würfel, Wolfgang; Bohlmann, Michael; Zschocke, Johannes; Rudnik-Schöneborn, Sabine; Nawroth, Frank; Schleußner, Ekkehard; Rogenhofer, Nina; Wischmann, Tewes; von Wolff, Michael; Hancke, Katharina; von Otte, Sören; Kuon, Ruben; Feil, Katharina; Tempfer, Clemens (Geburtshilfe und Frauenheilkunde, 2018)
Purpose Official guideline of the German Society of Gynecology and Obstetrics (DGGG), the Austrian Society of Gynecology and Obstetrics (ÖGGG) and the Swiss Society of Gynecology and Obstetrics (SGGG). The aim of this guideline was to standardize the diagnosis and treatment of couples with recurrent miscarriage (RM). Recommendations were based on the current literature and the views of the involved committee members.Methods Based on the current literature, the committee members developed the statements and recommendations of this guideline in a formalized process which included DELPHI rounds and a formal consensus meeting.Recommendations Recommendations for the diagnosis and treatment of patients with RM were compiled based on the international literature. Specific established risk factors such as chromosomal, anatomical, endocrine, hemostatic, psychological, infectious and immunological disorders were taken into consideration.Ziel Offizielle Leitlinie der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG), der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (ÖGGG) und der Schweizerischen Gesellschaft für Gynäkologie und Geburtshilfe (SGGG). Ziel der Leitlinie ist es, die Diagnostik und Therapie des wiederholten Spontanaborts (WSA) anhand der aktuellen Literatur sowie der Erfahrung der Mitglieder der Leitlinienkommission evidenzbasiert zu standardisieren.Methoden Anhand der internationalen Literatur entwickelten die Mitglieder der beteiligten Fachgesellschaften in einem formellen Prozess einen Konsensus. Empfehlungen und Statements der Leitlinie wurden in einem formalen Prozess (DELPHI-Prozess, Konsenstreffen mit moderiertem Abstimmungsprozess) erarbeitet und konsentiert.Empfehlungen Es wurden Empfehlungen zur Diagnostik und Therapie von Paaren mit WSA anhand der internationalen Literatur erarbeitet. Insbesondere wurde auf die bekannten Risikofaktoren wie chromosomale, anatomische, endokrinologische, gerinnungsphysiologische, psychologische, infektiologische und immunologische Störungen eingegangen.
Keywords: recurrent miscarriage; incidence; diagnosis; therapy; recommendations